“Paths not to Arrive but to Keep Walking”: A Post-qualitative Research on Critical Psychology in Cognitive Capitalism - Moreno, Fabio Giovanni; Peralta, María Claudia (Pensando Psicología, 2018)
Introduction: Self-referential, post-qualitative research was proposed to consider the current situation of researching professors at university, within the global context of cognitive capitalism and emphasizing the stands taken by a group of critical psychologists that would have been researching professors in schools of psychology in Colombia.Objective: To recognize ambivalent or contradictory senses and propose new meanings or emerging senses about critical psychology in Colombia, as well as the emerging role of the researching professor at current university through a post-qualitative methodology.Method: Through two concepts (différance and dissemination), reflecting on a set of autobiographies of four participants focused on their personal development as critical psychologists and researching professors.Result: Between the materials and the theorization conducted, we found that today critical psychology is more a transdiscipline than a branch or an approach of psychology. The participants’ affiliation to critical psychology is discontinuous; that is, when it occurs, it is more strongly associated with academic rhetoric, with a more institutional and work interest than with a purely epistemological or theoretical one. The repercussion of academic capitalism both in the schools of psychology and the current roles of teaching and research seems to be more detrimental in terms of academic quality and to the well-being of professors; however, researching professors also seem to tolerate and be silent about these repercussions.
Keywords: cognitive capitalism; post-qualitative research; critical psychology